Familial Mediterranean Fever with Neonatal Onset: Case Report. (15th December 2020) - Arslan, Kübra; Sarici, Serdar Ümit; Kolukisa, Gonca; Altun, Demet
Abstract : Familial Mediterranean fever (FMF) is an autosomal recessively inherited disorder characterized by recurrent fever and attacks of abdominal pain, chest pain, and joint pain. Attacks of recurrent fever and serositis are encountered clinically. Attacks may present either with only one symptom or many simultaneous symptoms. Although most of the patients are diagnosed clinically above the age of 2, those cases who are diagnosed before 2 years of age and with clinical course of isolated fever are believed to have a more serious course and tend to develop amyloidosis. In this article, a case who was admitted first on the 22nd day of life and later diagnosed to have FMF with recurrent attacks of isolated fever and no other focus is presented. We emphasize that FMF may present as early as in the first month of life, and it should be considered in cases presenting with fever of unknown origin and misdiagnosed to have late neonatal sepsis or occult bacteremia at this age group.